Stabilization and Fixation of Spondylolisthesis by Transforaminal Lumbar Interbody Fusion - TLIF : A Journey of Discovery (East West Medical College Journal, 2026)
Background: Spondylolisthesis is the forward displacement of a vertebra over a lower segment due to a congenital defect or fracture in the pars interarticularis, usually of the fifth lumbar over the sacrum, or of the fourth lumbar over the fifth. Spondylolisthesis is graded based upon the degree of slippage of one vertebral body relative to the subsequent adjacent vertebral body. Sings and symptoms ranges from Lower back pain, Sciatica, Back stiffness, Difficulty walking or standing for more than a few minutes at a time, numbness, weakness or tingling in feet. Surgical techniques and instrumentation provide surgeons with the means to substantially reduce spondylolisthetic deformity and restore spinal balance. Stabilizing the spondylolytic level is accomplished by arthrodesis in our case by a transforaminal approach and achieve excessive motion at the fused segment then Allowing the bone graft to heal and form a solid bone bridge between the vertebrae.Methods: A retrospective type of cohort study was done on 21 patients undergoing Transforaminal Lumbar Interbody Fusion- TLIF for spondylolisthesis with lumbar or lumbosacral spondylolisthesis in Zainul Haque Shikder Womens Medical College Hospital (ZHSWMCH), Dhanmondi, Dhaka under one Surgeon, study duration was from January 2023 to December 2024. Patient’s included in the study were Patients aged 18 years or older. Have evidence on magnetic resonance imaging of grade I and grade II spondylolisthesis. Having mechanical low back pain and radicular symptoms or were unresponsive to at least 6 months of conservative treatment.Results: Demographic distribution Number of male patients were 9 and female 12. Age group was ranging from 45 +- 6, hospital stay from the day of admission till discharge was 4 +- 1.2 after completion of treatment. Patients with spondylolisthesis in L4 - L5 and L5 - S1 were 10 and 11 respectively. Maximum number patients had Grade I slippage being 9 (42.86%), followed by 5 (23.81%) patients with Grade II, 4 patients with Grade III (19.05%), 2 patients with Grade IV (9.52%) and the least were with grade V being only 1 (4.76%) patient. Pre operative and post-operative VAS of back pain. Preoperatively patients VAS mean with standard deviation was 6.5+- 1.36 postoperative mean with standard deviation was 4.04+- 1.55. Preoperatively, 8 patients had severe disability according to ODI, 7 had moderate disability and 1 patient crippled disability. On the day of discharge, ODI showed 5 patients had minimal disability and 7 had moderate (there was no patient with severe or crippling disability). One week after discharge at follow up, 9 patients complained of minimal disability and 7 patients with moderate disability.Conclusion: TLIF surgery is an effective and precise treatment. It substantially reduced the possibility of infection-related complications and minimal damage to the muscles. Patients on undergoing TLIF surgery required fewer nights of hospital stay before returning home & fewer dependence on analgesics and had better postoperative outcomes.EWMCJ Vol. 14, No. 2, July 2026: 202-207